Efficient preservation of young terrestrial organic carbon in sandy turbidity-current depositsAbstract - Hage, S.; Galy, V.V.; Cartigny, M.J.B.; Acikalin, S.; Clare, M.A.; Gröcke, D.R.; Hilton, R.G.; Hunt, J.E.; Lintern, D.G.; McGhee, C.A.; Parsons, D.R.; Stacey, C.D.; et al. (Geology, 2020)
Burial of terrestrial biospheric particulate organic carbon in marine sediments removes CO2 from the atmosphere, regulating climate over geologic time scales. Rivers deliver terrestrial organic carbon to the sea, while turbidity currents transport river sediment further offshore. Previous studies have suggested that most organic carbon resides in muddy marine sediment. However, turbidity currents can carry a significant component of coarser sediment, which is commonly assumed to be organic carbon poor. Here, using data from a Canadian fjord, we show that young woody debris can be rapidly buried in sandy layers of turbidity current deposits (turbidites). These layers have organic carbon contents 10× higher than the overlying mud layer, and overall, woody debris makes up >70% of the organic carbon preserved in the deposits. Burial of woody debris in sands overlain by mud caps reduces their exposure to oxygen, increasing organic carbon burial efficiency. Sandy turbidity current channels are common in fjords and the deep sea; hence we suggest that previous global organic carbon burial budgets may have been underestimated.